PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA SELAMA PANDEMI COVID-19 PADA MATA PELAJARAN SKI : (Studi Kasus menggunakan metode survei di MA Nurul Iman Sindangkerta Bandung Barat) - Ayu Puji Rahayu (Jurnal Al Burhan, 2022)
This study aimed to determine and analyze the effect of online learning during the covid-19 pandemic on learning outcomes in the Islamic Cultural History subject at MA Nurul Iman Sindangkerta West Bandung. The research method used is a quantitative research method using surveys. The sampling technique used is the Krejcie sampling technique, with 40 respondents. While the data collection tool is an instrument in the form of a questionnaire. The data analysis technique used the help of SPSS version 25. Based on the results of data analysis, it was concluded that there was a significant influence of online learning during the covid-19 pandemic on learning outcomes in Islamic Cultural History subjects. The significant value evidences this in the coefficient table of 0.000. These results show the value of sig. less than alpha value = 0.05 or sig value 0.000 < = 0.05. This implies that Ho is rejected and Ha is accepted. So from the analysis of data processing, it can be concluded that there is a significant influence between online learning during the covid-19 pandemic on learning outcomes in Islamic Cultural History subjects at MA Nurul Iman Sindangkerta West Bandung students.